2019
DOI: 10.1108/tpm-12-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Why individual employee engagement matters for team performance?

Abstract: Purpose Adopting a multi-level research approach, this study aims to investigate the impact of employee engagement on team performance. It further explores the mediating effects of employee commitment and organizational citizenship behaviour on the employee engagement–team performance relationship. Design/methodology/approach The study follows a quantitative method. Data were collected through a self-administered questionnaire survey using snowball and convenience sampling. Descriptive statistics and bi-vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 118 publications
4
86
0
1
Order By: Relevance
“…PLS-based structural equation modeling (PLS-SEM) is used to analyze the data, which is popularly used in management science in the last four decades. Scholars recommended the PLS-based SEM model over simple regression because it guarantees the robustness of the result via investigating the entire model rather than testing each path alone [83][84][85].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…PLS-based structural equation modeling (PLS-SEM) is used to analyze the data, which is popularly used in management science in the last four decades. Scholars recommended the PLS-based SEM model over simple regression because it guarantees the robustness of the result via investigating the entire model rather than testing each path alone [83][84][85].…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 displays the reliability and validity scores of this study. Reliabilities showed that both Cronbach's alpha and composite reliabilities are above the minimum threshold limit of 0.70 [6,84,94]. Estimates showed the minimum Cronbach's alpha and composite reliability scores are 0.821 (performance expectancy), and 0.837 (effort expectancy), respectively.…”
Section: Measurement Model Evaluationmentioning
confidence: 96%
See 3 more Smart Citations